2017
DOI: 10.1590/1089-6891v18e-39597
|View full text |Cite
|
Sign up to set email alerts
|

Climate Spatialization and Genotype-Environment Interaction Effects on Weaning Weights of Nellore Cattle in Extensive Systems in Tropical Regions of Brazil

Abstract: Depending on the environmental differences among the regions, the phenotypic expression in beef cattle may significantly vary between the progenies of the same sire, and this is an important rule to identify the best animal. Thus, this study was carried out to spatialize environmental factors that may help to compare and discriminate the states of Maranhão, Pará, and Tocantins and also to check for genotype x environment interaction (G x E interaction) in these regions. The environmental variables analyzed wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…More recently Ferreira et al . (2017) and Rosé et al . (2017) showed that differences between temperate and tropical climates can cause significant genotype by environment interaction (G×E), which affects productivity.…”
Section: Discussionmentioning
confidence: 95%
“…More recently Ferreira et al . (2017) and Rosé et al . (2017) showed that differences between temperate and tropical climates can cause significant genotype by environment interaction (G×E), which affects productivity.…”
Section: Discussionmentioning
confidence: 95%
“…Breeding programs in developing countries are often ineffective as a consequence of the non-adaptability of the introduced breeds to the challenging environments Ojango and Pollott, 2002). More recently Ferreira et al (2017) and Rosé et al (2017) showed that differences between temperate and tropical climates can cause significant G x E which affects productivity. This breed-byenvironmental mismatch is usually estimated as genotype by environment interaction (G x E), the genetic correlation for a given set of traits estimated in two environments.…”
Section: Discussionmentioning
confidence: 99%